Developing A Process Framework For Managing The Realization Of Information Technology Benefits For Construction Companies - Kareem, Hassan Issa Abdul (2011)
Construction companies are spending large amounts of money being to realize IT. However, they are achieving less-than-expected benefits. This research explores the current procedures for realizing IT benefits, identifying realized IT benefits, identifying Critical Success Factors (CSFs) for managing the realization of IT benefits, and developing a conceptual process framework for managing the realization of IT benefits. The study based its conceptual framework on a comprehensive review of the literature on managing the realization of IT benefits.